2018
DOI: 10.1016/j.neuroimage.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory prefrontal cortex activity underlies stress-induced changes in Pavlovian fear conditioning

Abstract: Excessive stress exposure often leads to emotional dysfunction, characterized by disruptions in healthy emotional learning, expression, and regulation processes. A prefrontal cortex (PFC)-amygdala circuit appears to underlie these important emotional processes. However, limited human neuroimaging research has investigated whether these brain regions underlie the altered emotional function that develops with stress. Therefore, the present study used functional magnetic resonance imaging (fMRI) to investigate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
9
0
5
Order By: Relevance
“…Thus, our results suggest that there is an acute effect of trauma exposure that modulates the function of the dorsomedial PFC in regards to threat expectancy. Recent research demonstrates acute stress impacts neural activity within the dorsomedial PFC (Wheelock et al, 2016), which has subsequent effects on fear learning-related activity within this region of the brain (Goodman, Harnett, Wheelock, et al, 2018). Thus, acute posttraumatic stress may alter cognitive functions supported by the dorsomedial PFC that lead to changes in fear learning processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our results suggest that there is an acute effect of trauma exposure that modulates the function of the dorsomedial PFC in regards to threat expectancy. Recent research demonstrates acute stress impacts neural activity within the dorsomedial PFC (Wheelock et al, 2016), which has subsequent effects on fear learning-related activity within this region of the brain (Goodman, Harnett, Wheelock, et al, 2018). Thus, acute posttraumatic stress may alter cognitive functions supported by the dorsomedial PFC that lead to changes in fear learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior research has demonstrated that fear acquisition, expression, extinction, and extinction recall are disrupted in chronic PTSD (Blechert, Michael, Vriends, Margraf, & Wilhelm, 2007; Fani et al, 2012; Garfinkel et al, 2014; Grillon & Morgan, 1999; Milad et al, 2009; Norrholm et al, 2011). Further, previous research has demonstrated that acute stress exposure modulates associative fear learning (Goodman, Harnett, Wheelock, et al, 2018; Raio & Phelps, 2015), which is disrupted in chronic PTSD (Blechert et al, 2007; Fani et al, 2012; Garfinkel et al, 2014; Grillon & Morgan, 1999; Milad et al, 2009; Norrholm et al, 2011). For example, physical and psychosocial stress exposure appears to sensitize fear learning processes such that fear-related associations are formed more rapidly, and expressed more strongly and indiscriminately (Dunsmoor, Otto, & Phelps, 2017; Goodman, Harnett, Wheelock, et al, 2018; Rau, DeCola, & Fanselow, 2005; Shors, Weiss, & Thompson, 1992).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…An important goal of the current study was to assess potential stress reactivity during both V1 and V2, independently. As in previous work (Allendorfer et al, 2014(Allendorfer et al, , 2019Goodman et al, 2018Goodman et al, , 2019Orem et al, 2019), a preplanned contrasts of SMT and CMT (SMT -CMT) served as an index of increased BPM during stressful compared to control math conditions. In order to assess whether HR was greater during SMT compared to CMT during both visits, a priori planned contrasts compared HR for Task (CMT, SMT) at each level of Visit (V1, V2).…”
Section: Physiological Measuresmentioning
confidence: 92%
“…In addition to math performance measures, participant autonomic responses to MIST are commonly used to validate and index stress reactivity to the task (Allendorfer et al, 2014(Allendorfer et al, , 2019Wheelock et al, 2016;Elbau et al, 2018;Goodman et al, 2018Goodman et al, , 2019Gossett et al, 2018;Orem et al, 2019). In the present study, we sought to assess whether these measures indicated stress reactivity and whether this reactivity varied across repeated MRI visits.…”
Section: Physiological Responsesmentioning
confidence: 99%